2017
DOI: 10.1513/annalsats.201609-662oc
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Neighborhood, Race, and Sleep Apnea Severity in Children. A Six-City Analysis

Abstract: Neighborhood socioeconomic variables in comparison with individual-level socioeconomic indicators provides better explanations for the racial disparity in pediatric obstructive sleep apnea syndrome. Further research aimed at identifying factors that aggregate in disadvantaged neighborhoods and increase sleep apnea risk may suggest modifiable intervention targets. Clinical trial registered with clinicaltrials.gov (NCT00560859).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…More recently, builtenvironment and neighborhood-walkability features have been associated with sleep apnea (37). Neighborhood disadvantage, as quantified by census-track indicators of poverty, low education attainment, and family structure, has been associated with an increased risk of sleep apnea in children (38)(39)(40), but not yet in adults. These pediatric studies postulated that geographic differences in sleep disorders may relate to air quality, but did not have data to address this hypothesis.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…More recently, builtenvironment and neighborhood-walkability features have been associated with sleep apnea (37). Neighborhood disadvantage, as quantified by census-track indicators of poverty, low education attainment, and family structure, has been associated with an increased risk of sleep apnea in children (38)(39)(40), but not yet in adults. These pediatric studies postulated that geographic differences in sleep disorders may relate to air quality, but did not have data to address this hypothesis.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Thus far, limited data indicate that the risk of adverse health outcomes such as daytime sleepiness and cardiometabolic outcomes may also be higher in these populations. It is important to note that socioeconomic status (SES), neighborhood disadvantage, and poverty have been shown to mediate the elevated risk of OSA in AAs, underscoring the importance of considering and controlling for psychosocial factors in future studies of racial inequalities 5456 .…”
Section: Inequalities In Obstructive Sleep Apneamentioning
confidence: 99%
“…It must be noted that obesity, associated with OSA and CVD, is also disproportionately high in black population, as 63% of men and 77% of women in this ethnic group is either overweight or obese [11]. Per the Multi-ethnic study of atherosclerosis (MESA), black population demonstrated the highest levels of sleep disturbance, shorter sleep duration, worse sleep quality and daytime sleepiness compared to Caucasians, Hispanics and Asians [12]. Higher poverty rate is also associated with higher apnea-hypopnea index (AHI) with relatively lower continuous positive airway pressure (CPAP) therapy acceptance rate [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There are many proposed hypotheses as to why these discrepancies may exist, including poor access to health care services, non-adherence to treatment recommendations, inadequate training and environmental and genetic variations [12,15]. Although the existence of association in these conditions are widely acknowledged, the understanding of the roles in how these diseases influence each other is not well investigated.…”
Section: Introductionmentioning
confidence: 99%